Preservative treatment and chemical modification of bamboo for structural purposes - Gauss, Christian (2020)
Bamboo-based materials are in the toolbox of sustainable practices and have a high potential for the development and expansion of new products in the construction industry. Although uncountable advantages are attributed to bamboo, there are several problems related to its use that must be solved and mitigated. Without proper treatment, bamboo materials cannot withstand a long service life. The treatment procedures are already well-known, in which different methods and preservative solutions can be used depending on the final application, logistics, material condition, and affordability. Yet, necessary information about the chemical treatment of bamboo in terms of treatability, quality control, and the effect on physical-mechanical properties, and the development of less hazardous solutions are topics not adequately explored. Therefore, this doctorate thesis was divided into two major parts/objectives: assessment of conventional bamboo treatments and evaluation of alternative preservation methods based on chemical modification and in-situ polymerization. In the first part, conventional preservatives were applied for Dendrocalamus. asper and Phyllostachys edulis bamboo treatment and analysed in the quality aspects point of view. Analytical methods for treatability evaluation, such as penetration and retention, were used for disodium octaborate tetrahydrate (DOT) and chromate copper borate (CCB) treated bamboo. Mechanical, physical, and chemical tests were extensively used to characterize treated samples, and the effects of the preservatives on mechanical properties were investigated. Additionally, full-culm bamboo was object of detailed mechanical characterization through digital image correlation strain analysis. The obtained results led in recommendations for future standards for bamboo testing and the observation of the local effect of the node on compression, shear, tension, and bending. Besides, the investigated treatments did not show detrimental effects on the mechanical properties, yet DOT treatment causes an improvement in bamboo strength. Guidelines for treatment by the immersion method using DOT are also proposed to ensure the production quality of treated bamboo. In the second part of this thesis, pursuing the objective to improve the overall properties of bamboo, alternative treatment formulations based on citric acid and tannin in combination with boron compounds were tested. Samples chemically modified with citric acid presented considerable improvement on dimensional stability and decrease of water absorption as the consequence of an esterification process. However, the modification increased bamboo brittleness, reducing especially tension and bending strengths. The use of polymerized tannin/hexamine/boron had positive outcomes on the overall properties of bamboo, increasing the compression and bending strengths and the fungi degradation resistance even after leaching. Moreover, although DOT was effective in improving fungi decay resistance, severe leaching completely decreased its fungicide activity. Through thermogravimetric analyses, boron treated samples exhibited better thermal stability. In general, bamboo is a fascinating material. Nevertheless, although satisfactory treatment can be achieved, it is more difficult to be treated and characterised than wood. To overcome these problems, more research in characterization and treatment methods are necessary for better understanding and use of this abundant and versatile material.